Civil Society and Political Representation in Latin America (2010-2015) Towards a Divorce Between Social Movements and Political Parties? (Springer International Publishing, 2018)
This book presents in-depth analyses of the wave of political protest and unrest that spread throughout Latin America between 2010 and 2015 in order to answer a question that has been challenging social scientists all over the region: why some countries have faced a divorce between their social movements and political parties while others have not? The contributions gathered in this volume intend to show that the logic of political representation in Latin America and its supposed "crisis" is not a common and constant feature for all region. Some countries like Chile, Brazil, Colombia and Mexico seem to have experienced a process of autonomization of its social movements vis-à-vis its institutional political system. However, Argentina, Bolivia, Ecuador and Uruguay have not seen such a split between civil society and the political parties. Bringing together eight case studies of the countries mentioned and a general assessment of the situation in the whole region, this book presents some interesting findings that will contribute to the discussions about the political representation crisis in Latin America, providing valuable resources for political leaders, researchers, policy makers and social activists in the region.